Management of Natural Resources Based on Local Wisdom by Traditional Law Communities - Triono Eddy (CV. Inara, 2021)
Natural resources are gifts and mandates given by Allah SWT to the Indonesian people as priceless wealth. The availability of natural resources, both biological and non-biological, is very limited. Therefore, these natural resources must be managed wisely so that they can be used in an efficient, effective and sustainable manner for the greatest prosperity of the people and can even continue to be enjoyed and felt by the present generation and for generations to come. This research was conducted with a normative research method. Normative research is a scientific research procedure to find the truth based on scientific logic from the normative side. Recognition and respect for customary law communities and traditional communities can be realized in the form of protection and empowerment in accordance with their characteristics. This can be seen in the still scattered and scattered regulations regarding indigenous peoples in natural resource management which are sectoral in nature so that they have not accommodated the legal needs of indigenous peoples.